Socialization of Cash Waqf Management in Universities in Malaysia - Riyaldi, Muhammad Haris; Syahrizal, Teuku Muhammad; Halim, Hendra; Othman, Razali Bin; Umuri, Khairil; Sari, Nurma; Nurlina, Eka; Farid; Susanna; Sartiyah; Rani, Dzacky Muharram (IJCS: International Journal of Community Service, 2024)
This community service activity titled "Socialization of Cash Waqf Management in Universities in Malaysia" is a collaboration between the Islamic Economics Program, Faculty of Economics and Business, Syiah Kuala University, and Waqf Advisory Consultancy, Malaysia. The activity aims to enhance the understanding and skills of lecturers and students in managing cash waqf professionally and in accordance with sharia principles. Conducted on Tuesday, June 28, 2024, from 09.00 to 11.00 Malaysian time at Sakura Elite Hotel, Kuala Lumpur, Malaysia, the event featured Dr. Razali Bin Othman from Waqf Advisory Consultancy, Malaysia, as the keynote speaker. Utilizing the service learning (SL) method, the activity involved lecturers and students from the Islamic Economics Program as participants. Pre-test and post-test evaluations showed a significant increase in participants' understanding of cash waqf management, with comprehension rising post-activity. Participants also demonstrated increased practical skills and high satisfaction with the materials presented. The results indicate that the participants are ready to apply the knowledge gained, with some proposing cash waqf projects in their universities. The activity supports the achievement of the SDGs, particularly Goal 4 (Quality Education) and Goal 17 (Partnerships for the Goals). Despite some challenges such as limited time and technical issues with digital platforms, the activity successfully met its objectives and provides a model for similar future initiatives. This community service activity contributes to the development of knowledge and technology in cash waqf management and fosters its application in academic settings and beyond.